Estradiol's beneficial effect on murine muscle function is independent of muscle activity - Greising, Sarah M. (American Physiological Society, 2011)
Estradiol (E(2)) deficiency decreases muscle strength and wheel running in female mice. It is not known if the muscle weakness results directly from the loss of E(2) or indirectly from mice becoming relatively inactive with presumably diminished muscle activity. The first aim of this study was to determine if cage activities of ovariectomized mice with and without E(2) treatment differ. Ovariectomized mice were 19–46% less active than E(2)-replaced mice in terms of ambulation, jumping, and time spent being active (P ≤ 0.033). After E(2)-deficient mice were found to have low cage activities, the second aim was to determine if E(2) is beneficial to muscle contractility, independent of physical activities by the mouse or its hindlimb muscles. Adult, female mice were ovariectomized or sham-operated and randomized to receive E(2) or placebo and then subjected to conditions that should maintain physical and muscle activity at a constant low level. After 2 wk of hindlimb suspension or unilateral tibial nerve transection, muscle contractile function was assessed. Soleus muscles of hindlimb-suspended ovariectomized mice generated 31% lower normalized (relative to muscle contractile protein content) maximal isometric force than suspended mice with intact ovaries (P ≤ 0.049). Irrespective of whether the soleus muscle was innervated, muscles from ovariectomized mice generated ∼20% lower absolute and normalized maximal isometric forces, as well as power, than E(2)-replaced mice (P ≤ 0.004). In conclusion, E(2) affects muscle force generation, even when muscle activity is equalized.